Fostering Critical Thinking through Integrating Edpuzzle in Blended Learning - Djoko Sutrisno; Abbas, Azwar (Mutiara Intelektual Indonesia Press, 2023)
To better prepare students for the demands of the twenty-first century, the Ministry of Education and Culture of the Republic of Indonesia incorporates character education into a range of educational courses. English as a foreign language, teachers can select the chosen learning approach for their students—which might require using critical thinking skills—by using digital interactive media like Edpuzzle. This study's goal was to evaluate how digital interactive media like Edpuzzle were used in online English as a foreign language (EFL) classes and how it affected the students' critical thinking abilities. In order to help students enhance their critical thinking abilities in the context of problem-solving related to various learning styles, this project intends to create digital media based on character values. The 4-D approach was used in this product development study (Define, Design, Develop, and Disseminate). The digital interactive media Edpuzzle obtained a total average score of 3.60 based on the validation from the material expert and a score of 3.50 based on the evidence from the media expert, indicating that the study's findings are correct. 92% of the eighth-graders reactions were positive, per the assessments. Active learning during the teaching process also causes the students to feel positive emotions. Students can also develop their ability to think critically by speaking out in class and having meaningful debates with their classmates